2004
DOI: 10.1080/1355785042000250111
|View full text |Cite
|
Sign up to set email alerts
|

How Do Older Chinese Women View Health and Cancer Screening? Results from Focus Groups and Implications for Interventions

Abstract: Our results suggest traditional Chinese beliefs, such as those pertaining to fatalism, self-care, and the hot and cold balance, influence the perceptions of older Chinese women regarding health, illness, and use of preventive healthcare. Interventions to improve cancer screening in this population should be tailored to the specific predisposing, enabling, and reinforcing factors of this population, including cultural views, language barriers, doctor-patient communication, and access to healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
142
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 5 publications
4
142
0
Order By: Relevance
“…The men who used crisis intervention were less likely to seek cancer screening than those who used preventive approach; those who preferred to use Eastern medicine for health care were more likely to seek for prostate cancer screening. The use of Eastern medicine may indicate that these immigrants misunderstand and/or mistrust Westernized health care and medicine, reducing their engagement and participation in treatment [33]. This is evidence that cultural beliefs play a part in health screening decisions.…”
Section: Challenges To Immigrants: the Importance Of Health Literacy mentioning
confidence: 99%
“…The men who used crisis intervention were less likely to seek cancer screening than those who used preventive approach; those who preferred to use Eastern medicine for health care were more likely to seek for prostate cancer screening. The use of Eastern medicine may indicate that these immigrants misunderstand and/or mistrust Westernized health care and medicine, reducing their engagement and participation in treatment [33]. This is evidence that cultural beliefs play a part in health screening decisions.…”
Section: Challenges To Immigrants: the Importance Of Health Literacy mentioning
confidence: 99%
“…22 Responses to each item were assessed on a 5-point Likert scale, ranging from strongly agree, agree, neutral, disagree, to strongly disagree. Rotated principal component factor analyses showed that these items measured cultural domains, such as fatalism, self-care, hot-cold balance, use of herbs, Western medicine, medical checkups, and lifestyle, with an internal consistency score (Cronbach's alpha) between 0.82 and 0.39.…”
Section: Methodsmentioning
confidence: 99%
“…Chinese physicians may also choose not to discuss screening, assuming that Chinese women are reluctant to discuss cancer or discuss body parts, such as breasts and the cervix. 22 On the other hand, some women visiting English-speaking physicians may have been accompanied by an interpreter, a variable not included in the survey, which adds to the complexity of the communication process. Future research is needed to determine which of these possible factors explain our results.…”
Section: Factors Associated With Physicians' Cancer Screening Recommementioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Cultural research suggests that these values may keep Chinese individuals from seeking Western medicine for help, and they influence conceptions of illness and cancer. [12][13][14][15][16][17][18] To improve Chinese American participation in biospecimen research, the current study builds on a needs assessment of Philadelphia Chinese Americans using Community-Based Participatory Research (CBPR) approaches.The purpose of this article is to determine how demographics, health care access, knowledge, and cultural beliefs are associated with willingness to participate in biospecimen research among Chinese Americans.…”
mentioning
confidence: 99%